2018
DOI: 10.1111/jon.12585
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound, Clinical, and Electrophysiological Findings in Persistent Carpal Tunnel Syndrome

Abstract: BACKGROUND AND PURPOSE We present the clinical, electrophysiological, and nerve ultrasound findings in cases of persistent carpal tunnel syndrome (PCTS). METHODS Eighteen PCTS patients underwent evaluation with the Boston Carpal Tunnel Syndrome Questionnaire (BCTSQ), electrophysiology, and nerve ultrasound with a mean of 3.5 months (SD ± 1.4) after open surgery. RESULTS PCTS patients showed a mean symptom severity scale score of 3.1 (SD ± 1.1) and functional severity scale score of 3.2 (SD ± 0.9) in BCTSQ. Ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Oliveira et al [ 23 ] found that the patient first felt numbness or pain in the three fingers of the radius, holding weakness, with the middle finger, and the heaviest symptoms at night or in the morning, appropriate symptoms of shaking the wrist can be reduced, and wrist Tinel and Phalen signs are positive. Kerasnoudis et al [ 24 ] found that big fish between electromyography and wrist refers to the median nerve conduction speed determination of nerve damage; although electrophysiological diagnosis is a special diagnostic standard of wrist syndrome, but it cannot provide necessary help for surgery, cannot look directly around the median nerve, high-frequency ultrasound can well show the median nerve and wrist tendon and is conducive to find the cyst, schwannoma, lipoma, hematoma, and other causes of carpal tunnel syndrome [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oliveira et al [ 23 ] found that the patient first felt numbness or pain in the three fingers of the radius, holding weakness, with the middle finger, and the heaviest symptoms at night or in the morning, appropriate symptoms of shaking the wrist can be reduced, and wrist Tinel and Phalen signs are positive. Kerasnoudis et al [ 24 ] found that big fish between electromyography and wrist refers to the median nerve conduction speed determination of nerve damage; although electrophysiological diagnosis is a special diagnostic standard of wrist syndrome, but it cannot provide necessary help for surgery, cannot look directly around the median nerve, high-frequency ultrasound can well show the median nerve and wrist tendon and is conducive to find the cyst, schwannoma, lipoma, hematoma, and other causes of carpal tunnel syndrome [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study is thus complementary to a prior investigation which showed conversely that WFR did not improve in 16 of 18 cases with poor outcomes, although that study did not focus on severe CTS. 17 Ultrasound has the additional benefit of anatomical evaluation of the transverse carpal ligament to rule out incomplete release, 18 as well as to evaluate possible additional compressive structures, such as ganglion cysts or forearm lesions, and other anomalies, such as persistent median artery, bifid median nerve, and palmaris profundus. 8 Another potential benefit of ultrasound evaluation after carpal tunnel release is objective demonstration of improvement in cases that may be confounded by issues beyond carpal tunnel pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative assessment of the median nerve and carpal tunnel can reveal helpful findings, including a focally narrowed nerve in longitudinal view (“notch sign”), scar tissue above the nerve (Fig. 1A), an incompletely released flexor retinaculum, neuroma, or other pathology that may identify the cause and the need for re-exploration in patients with a poor surgical outcome 47,49,52–54 . These findings have not been studied in a systematic manner and may not be useful to most sonographers, but experts in NMUS use it routinely in this setting 5,9 .…”
Section: Specific Conditionsmentioning
confidence: 99%
“…1A), an incompletely released flexor retinaculum, neuroma, or other pathology that may identify the cause and the need for re-exploration in patients with a poor surgical outcome. 47,49,[52][53][54] These findings have not been studied in a systematic manner and may not be useful to most sonographers, but experts in NMUS use it routinely in this setting. 5,9 Further study is required to show that qualitative differences between patients with good and poor outcomes are seen in a blinded manner with statistical significance.…”
Section: Focal Mononeuropathies Carpal Tunnel Syndromementioning
confidence: 99%